PERSPECTIVES ON PATIENT CENTERED CARE: A SURVEY OF GHANAIAN PHYSIOTHERAPISTS (International Journal of Physiotherapy, 2015)
Background: Implementation of patient-centered care (PCC) in health-care has been shown to improve safety, trust, health outcomes and adherence. There is however a dearth of literature on perspectives around PCC with specific regard to physiotherapy. This study aimed at investigating the perspectives of Ghanaian physiotherapists on patient-centered care in relation to its meaning, attitude and limitations.Methods: A questionnaire design was used. A questionnaire comprising both closed and open-ended questions was used to collect data from Ghanaian physiotherapists via post and e-mail. A response rate of 60% was recorded. Data was analyzed using descriptive statistics and framework analysis.Results: Majority (97%) of physiotherapists indicated practicing a PCC approach is important. Nine (9) themes arose regarding the meaning of PCC. Superficial understanding was present across most respondents. Misinterpretation of the meaning of PCC was also recorded from few respondents. Communication and education were the perceived most important and practiced PCC approaches. The least practiced approaches were determining number of treatment by patient preferences and departmental standards and administering patient preferred treatment choice. Twelve (12) themes arose from the limitations to PCC. The greatest limitation to PCC was found to be poor therapist-to-patient ratio.Conclusion: Ghanaian physiotherapists perceive PCC to be an important approach. Well known aspects of PCC are practiced and aspects regarding consideration of patient preferences are not practiced. The Ghanaian physiotherapist-patient experience is largely paternalistic. An increased awareness and understanding of PCC might translate into better implementation of PCC.